(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Data Warehouse is a collection of large amount of data which is used by the management for making strategic decisions. The data in a data warehouse is gathered from heterogeneous sources and then populated and queried for carrying out the analysis. The data warehouse design must support the queries for which it is being used for. The design is often an iterative process and must be modified a number of times before any model can be stabilized. The design life cycle of any product includes various stages wherein, testing being the most important one. Data warehouse design has received considerable attention whereas data warehouse testing is being explored now by various researchers. This paper discusses about various categories of testing activities being carried out in a data warehouse at different levels